Exploring EFL Learners' Writing Introduction of Research Proposal: Difficulties and Solutions - Amri, Samsul; Salmiati, Salmiati (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
This study aims to investigate EFL learners’ difficulties in writing the introduction to a research proposal. We conducted this study using a survey research design. The subjects of this study were thirty-six learners and the instrument used is a questionnaire. The findings revealed that the learners' total score for agreement with the challenges in writing the Introduction section of a research proposal was 117.75, indicating neutral conditions. It was confirmed by an overall percentage of 65.4%. It indicates that learners do not have a strong judgment about the difficulties of writing an introduction to a research proposal. This neutral condition could indicate perplexity, doubt, or a lack of trust in their abilities. The most difficult components for learners were explaining the origins of the problem or topic in their introduction section, as well as presenting an explanation for the gap. They use some of the best methods to solve their problems, such as reading a lot of relevant sources, discussing with the professor, friends, or others, and employing technology. It is intended that by giving additional help, support, and relevant resources, learners will be able to overcome these challenges and improve their writing skills.